Cryopreservation of human spermatozoa by freezing testicular seminiferous tubule with novel cryopiece. (26th December 2021) - Lin, Feng; Zheng, Beihong
Abstract: This study was carried out to evaluate the effectiveness of cryopreservation of human spermatozoa by freezing testicular seminiferous tubule with a new cryocarrier named 'novel cryopiece'. Testicular tissue (TT) was collected from patients who underwent diagnostic testicular biopsy. Overall, 35 TT samples were obtained. Each TT sample was equally divided into four groups named (e.g. G1, G2, G3 and Gc). G1 was frozen as testicular seminiferous tubule using novel cryopiece, G2 was frozen as testicular cell suspensions using novel cryopiece, G3 was frozen as testicular cell suspensions using 0.25 ml straw, and Gc was not frozen. The samples in G1 and G2 experimental groups were cryopreserved in five separate aliquots and stored in the same cryovial. The freeze–thaw sperm DNA fragmentation index (DFI) of G2 was lower than that of G3 (20.27 ± 5.40 vs 23.55 ± 6.02; p  = 0.004). After thawing, spermatozoa could be found in all 35 testicular seminiferous tubule specimens in G1; however, it could not be found in 2 of 35 (5.7%) and 1 of 35 (2.9%) testicular cell suspensions samples in G2 and G3 respectively. This study indicates that novel cryopiece presented for the cryopreservation of testicular seminiferous tubules and testicular cell suspension is simple and effective.